Evaluasi Program Pemberian Makanan Tambahan Telur Fungsional Pada Ibu Hamil Kekurangan Energi Kronis (KEK) di Wilayah Kabupaten Sleman (Berita Kedokteran Masyarakat (BKM), 2020)
Objective: To determine the effect of functional egg administration on changes in nutritional status, protein intake, and babies born. Methods: A study analytical with cross sectional design that was seen retrospectively. To support research data, in-depth interviews were conducted with key informants and research supporters. Results: Analysis found that consumption of functional eggs was not statistically related to nutritional status, weight and length of the child's body but was related descriptively. Functional egg consumption is associated with an increase in energy and protein intake with p values 0.005 and 0, 011 (p <0.05).Conclusion: There was an increase in body weight, MUAC and nutritional status of CED pregnant women became NON CED, thereby reducing the birth of LBW and LBL. Functional eggs have not been used as additional food, but instead become the main protein intake of the mother. There is a need to increase commitment among organizers, implementers and targets in implementing programs to break the stunting chain.Keywords: CED, Functional Egg Supplementary Feeding Program, Stunting